Challenges in the implementation of public electronic services: lessons from a regional-based study - Ferreira, Neuza C. M. Q. F.; Ferreira, Fernando A. F.; Marques, Carla S. E.; Pérez-Bustamante Ilander, Guillermo O.; Çipi, Amali (Journal of Business Economics and Management, 2015)
Building the information and knowledge society has involved the development of numerous projects and initiatives all over the world. Portugal is no exception. This work is based on the analysis of the ALO Digital Project, which involves a series of strategies developed at the local e-government level in four Portuguese counties near Lisbon (i.e. Amadora, Loures, Odivelas and Vila Franca de Xira). Having the residents of the four counties involved as the target, this paper aims to identify the level of electronic service use resulting from the implementation of the ALO Digital Project. A questionnaire was administered and the results of a regression analysis demonstrate that the project is still at low level of online service sophistication. Additionally, despite users’ overall satisfaction, implementation difficulties were noticed. In practical terms, this reveals a type of service more related to information consultation, downloading and printing documentation, and supports the premise that a change of focus and direction of local e-government is needed to substantially improve the life of the individual citizen.